(untitled) (The Journal of DMC, 2026)
The citizen charter is a formal commitment by a governmental office to the public, outlining services, standards, and institutional responsibilities to promote transparency, accountability, and responsiveness. Its effectiveness depends on public awareness and institutional compliance. This study examines citizens’ awareness of the citizen charter and the quality of service delivery at the District Administration Office (DAO), Surkhet. Grounded in principles of good governance and public service effectiveness, the study employed a qualitative design. Data were collected through interviews and observations involving selected service users and providers. The findings reveal that the citizen charter is visibly displayed and systematically practiced at the DAO. Services were generally perceived as timely, procedurally clear, and of satisfactory quality. However, political, administrative, and personal factors occasionally affected service outcomes. Awareness was comparatively low among uneducated and marginalized groups. The study contributes to the literature on public service governance by providing empirical evidence on the implementation effectiveness, citizen awareness, and service delivery performance of the citizen charter. It highlights both institutional strengths and inclusivity gaps that inform policy improvement and accountability reforms.